(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aims to describe the prevalence of anxiety, depression, and stress among healthcare workers at Phu Binh district General Hospital, Thai Nguyen province, in 2024. Subject and methods: A cross-sectional descriptive study was conducted on 134 healthcare workers at Phu Binh district General Hospital, Thai Nguyen province, from April to December 2024. The DASS-21 scale was used to assess symptoms of anxiety, depression, and stress. Results: The prevalence of anxiety, depression, and stress among healthcare workers was 13.4%, 25.4%, and 28.8%, respectively. Most of the disorders were mild in severity, with mild anxiety accounting for 72.2%, mild depression 58.8%, and mild stress 63.2%. The proportion of workers experiencing severe levels was 0.74% for anxiety, 4.48% for depression, and 2.24% for stress. Among those with psychological disorders, 32.8% had a single disorder-stress alone was the most common at 17.9%. Additionally, 12.7% had two co-occurring disorders, and 3% experienced all three. Conclusion: It is necessary to implement strategies to protect and promote mental health among healthcare workers, with particular attention to conditions with higher severity and prevalence such as depression and stress